2000
DOI: 10.1098/rspb.2000.1258
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory coding in a simple system: adaptation inDrosophilalarvae

Abstract: Drosophila melanogaster larvae were pre-stimulated with high concentrations of six homologous alcohols (C4^C9) and then tested for adaptation and cross-adaptation using these same alcohols, four aliphatic n-acetates and three acids. Pre-stimulation with hexanol e¡ectively reduced to zero (abolished) test responses to all six alcohols, whereas test responses to hexanol were only a¡ected by pre-stimulation with hexanol. This substance appears to play a fundamental role in the organization of the larval olfactory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 34 publications
4
56
0
Order By: Relevance
“…1-Hexanol caused a dose dependent increase in attraction and was the compound that induced the highest target vector response values from Lobesia larvae. This attraction indicates that 1-hexanol plays a fundamental role in the olfactory responses of these larvae, as has also been found for Drosophila melanogaster larvae (Cobb and Domain, 2000;Oppliger et al, 2000). 1-Hexanol was also tested here in 1:1 (v/v) binary mixtures with host plant compounds of other chemical classes.…”
Section: Behavioural Response To the Odour Of The Artificial Diet Andmentioning
confidence: 99%
“…1-Hexanol caused a dose dependent increase in attraction and was the compound that induced the highest target vector response values from Lobesia larvae. This attraction indicates that 1-hexanol plays a fundamental role in the olfactory responses of these larvae, as has also been found for Drosophila melanogaster larvae (Cobb and Domain, 2000;Oppliger et al, 2000). 1-Hexanol was also tested here in 1:1 (v/v) binary mixtures with host plant compounds of other chemical classes.…”
Section: Behavioural Response To the Odour Of The Artificial Diet Andmentioning
confidence: 99%
“…The method that we apply to detect input-driven adaptation may be viewed as a variant of the cross-adaptation technique (McBurney et al, 1972;Cobb and Domain, 2000;Heinrich and Bach, 2002). This is frequently used to investigate whether the processing of different stimuli occurs along a common pathway; if adaptation to one stimulus carries over to another, a common pathway can be assumed.…”
Section: Experimental Approach To Detecting Input-driven Adaptationmentioning
confidence: 99%
“…The Drosophila larval olfactory system is much smaller and simpler by comparison (Cobb and Domain, 2000;Heimbeck et al, 1999), shown to consist of only 21 ORNs in the dorsal organ (Singh and Singh, 1984) and believed to include ~50 PNs relaying information to the larval MB and LH (Python and Stocker, 2002;Stocker, 1994). Developmental analysis has shown that the PNs born during larval stages exhibit only a single unbranched process from the cell body to the MB calyx until early metamorphosis, when dendrites and axon terminal branches start to elaborate (Jefferis et al, 2004).…”
Section: Introductionmentioning
confidence: 99%